Canine Brucellosis: An Update - Santos, Renato L.; Souza, Tayse D.; Mol, Juliana P. S.; Eckstein, Camila; Paíxão, Tatiane A. (Frontiers in Veterinary Science, 2021)
Canine brucellosis is an infectious and zoonotic disease caused by Brucella canis, which has been reported worldwide, and is a major public health concern due to close contact between dogs and humans. In dogs, canine brucellosis manifests with abortion outbreaks, reproductive failure, enlargement of lymph nodes, and occasionally affects the osteoarticular system, although the occurrence of asymptomatic infections in dogs are not uncommon. In humans, the disease is associated with a febrile syndrome, commonly with non-specific symptoms including splenomegaly, fatigue, and weakness. Infection of dogs occurs mostly by the oronasal route when in contact with contaminated tissues such as aborted fetuses, semen, urine, and vaginal secretions. In humans, contact with contaminated fluids from infected dogs is an important source of infection, and it is an occupational risk for veterinarians, breeders, laboratory workers, among other professionals who deal with infected animals or biological samples. The diagnosis in dogs is largely based on serologic methods. However, serologic diagnosis of canine brucellosis remains very challenging due to the low accuracy of available tests. Molecular diagnostic methods have been increasingly used in the past few years. Treatment of infected dogs is associated with a high frequency of relapse, and should be employed only in selected cases. Currently there are no commercially available vaccines for prevention of canine brucellosis. Therefore, development of novel and improved diagnostic methods as well as the development of efficacious and safe vaccination protocols are needed for an effective control of canine brucellosis and its associated zoonotic risk.